A coupled flood-agent-institution modelling (CLAIM) framework for urban flood risk management. (January 2019) - Abebe, Yared Abayneh; Ghorbani, Amineh; Nikolic, Igor; Vojinovic, Zoran; Sanchez, Arlex
Abstract: In this paper, we describe a modelling framework that allows the integration of human and physical components of flood risk. Within this framework, flood risk management is conceptualized as a coupled human-flood system. The human subsystem includes individuals and their behaviour and institutions that shape human-flood interaction. The framework presents a dynamic integration between agent-based models of individuals and institutions and numerical flood models. We demonstrate the framework's modelling application by examining the effects of three institutions in the Caribbean island of Sint Maarten. The case study shows the capabilities of the framework by exploring impacts of existing policies on flood risk reduction. Coupled agent-based-flood models built using the framework are useful to analyse policy options that address flood hazard and communities' vulnerability and exposure to support policy decision making. These models also show how flood risk changes over time in relation to the human dynamics on the urban environment. Highlights: CLAIM framework integrates actors, institutions, urban environment, physical processes and external factors. CLAIM methodology explains procedures to build coupled agent-based-flood model. Coupled agent-based-flood models simulate human-flood interactions and evaluate flood risk management policy options. Case study illustrates how agents' responses to institutions influence flood hazard, and their vulnerability and exposure.